VIRTUAL LEARNING PLATFORM IN ARCHITECTURE DESIGN STUDIO FOR MAINTAINING AUTONOMY AND AUTHORITY - Harahap, Mochammad Mirza Yusuf; Atmodiwirjo, Paramita (architecture department, Engineering faculty, Universitas Diponegoro, 2021)
This paper highlights a strategy for design studio learning due to the restriction during the COVID-19 pandemic that requires an immediate change from physical, face-to-face learning to virtual, online learning. The study examines how creative design and knowledge construction could be monitored throughout the learning process in the virtual studio. The study reflects upon the autonomy and authority of students and tutors, respectively, as they utilise a particular platform for virtual learning. The virtual communication platform becomes the media to accommodate reflection, peer learning, benchmarking and constructive feedback as essential parts of design learning. The study argues that it is essential to establish a strategy to balance the tutor’s space in maintaining their authority and the students’ space in building their autonomy as a design learner in the virtual studio environment.